Anterior-posterior subdivision and the diversification of the mesoderm in Drosophila. - Dunin-Borkowski, O.M.; Brown, N.H.; Bate, M. (Development, 1995)
We have used a novel cell marker, in which the twist promoter directs the synthesis of the cell surface protein CD2 (twi-CD2) to examine the development of the mesoderm in the Drosophila embryo after gastrulation and to locate the progenitor cell populations for different mesodermal derivatives. We find that the early mesoderm in each segment is divided into a more anterior region with relatively low levels of twist and twi-CD2 expression and a more posterior region where twist and twi-CD2 expression are high. This subdivision coincides with regional assignments of cells to form different progenitors: dorsal anterior cells invaginate to form an internal layer from which the visceral mesoderm is derived. Ventral anterior cells form progenitors of mesodermal glial cells. Dorsal posterior cells form heart. Ventral and dorsal posterior cells form somatic muscles. We conclude that the metamerically repeated anterior-posterior subdivision of the mesoderm is an essential element in laying out the pattern of mesodermal progenitor cells and in distinguishing between an internal cell layer which will give rise to the progenitors of visceral muscles and an external layer which will generate the somatic muscles and the heart.